Enhancing Qur'anic and Hadith Understanding Through EAMS-Games-Tournaments (TGT) at MIS Al Hidayah - Kurniawati Holilah; Rumhayati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' understanding of the Qur'an and Hadith at MIS Al Hidayah by integrating the Educational Achievement Motivation Strategies (EAMS) and Games-Tournaments (TGT) approach. The study addresses the challenge of making Islamic studies, particularly the Qur'an and Hadith, more engaging and effective for students at the elementary level. By combining educational motivation techniques with interactive learning methods, the research intends to enhance students' interest, participation, and comprehension of these fundamental Islamic texts. The EAMS-TGT approach encourages active involvement, friendly competition, and teamwork, which are expected to improve both academic achievement and spiritual development. The research is conducted in two cycles, with each cycle including planning, action, observation, and reflection phases. Data is collected through classroom observations, quizzes, and interviews with both students and teachers. The results indicate that the EAMS-TGT approach significantly increased students' motivation and participation during lessons. Students exhibited higher engagement levels, especially in activities related to the Qur'an and Hadith, demonstrating a deeper understanding of the material. Teachers also reported improved classroom dynamics, with more collaborative learning and enhanced student-teacher interaction. This study highlights the potential of combining traditional Islamic education with modern interactive learning methods to make Qur'anic and Hadith studies more accessible and enjoyable for young learners. It suggests that incorporating motivational strategies and interactive games can significantly improve the learning experience and outcomes in Islamic education. The findings provide valuable insights for educators looking to innovate their teaching methods and foster a more dynamic and engaging classroom environment.